2017
DOI: 10.1155/2017/3151694
|View full text |Cite
|
Sign up to set email alerts
|

Application of Real-Time 3D Navigation System in CT-Guided Percutaneous Interventional Procedures: A Feasibility Study

Abstract: Introduction To evaluate the accuracy of a quantitative 3D navigation system for CT-guided interventional procedures in a two-part study. Materials and Methods Twenty-two procedures were performed in abdominal and thoracic phantoms. Accuracies of the 3D anatomy map registration and navigation were evaluated. Time used for the navigated procedures was recorded. In the IRB approved clinical evaluation, 21 patients scheduled for CT-guided thoracic and hepatic biopsy and ablations were recruited. CT-guided procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…The average needle placement accuracy in the liver phantom was 2.0 ± 0.7 mm – 2.8 ± 1.1 mm and 3.0 ± 1.4 mm in the lung. In the clinical setting, the accuracy was 4.6 ± 3.1 for all procedures [ 20 ]. Mbalisike et al evaluated a robotic system (MAXIO, Perfint Healthcare, Indiana, USA) for applicator placement in MWA on patient that had been treated with trans-arterial chemoembolization (TACE) within 3 months prior to MWA.…”
Section: Discussionmentioning
confidence: 99%
“…The average needle placement accuracy in the liver phantom was 2.0 ± 0.7 mm – 2.8 ± 1.1 mm and 3.0 ± 1.4 mm in the lung. In the clinical setting, the accuracy was 4.6 ± 3.1 for all procedures [ 20 ]. Mbalisike et al evaluated a robotic system (MAXIO, Perfint Healthcare, Indiana, USA) for applicator placement in MWA on patient that had been treated with trans-arterial chemoembolization (TACE) within 3 months prior to MWA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have shown that the use of a stereotactic CT-based navigation systems in placing applicators for MWA and RFA is safe and accurate 6 , 7 , 10 12 . Furthermore, several studies have shown the use of stereotactic navigation in IRE treatment with good results 13 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Navigation systems have been used in neurosurgery and orthopaedic surgery[43,44]. In liver oncologic surgery the navigation solutions seem to have a reliable implication in interventional liver radiology[45,46]. In open and laparoscopic liver surgery the navigation systems are based in the combination of preoperative imaging, IUS and tracking systems with sophisticated intraoperative instrumentation (Figure 5)[3,35,47].…”
Section: Navigation Systemsmentioning
confidence: 99%